Human Papillomavirus Types 16 and 18 mRNA Levels and Not DNA Levels May be Associated With Advancing Stages of Cervical Cancer. Issue 8 (1st November 2009) - Gnanamony, Manu; Peedicayil, Abraham; Subhashini, John; Ram, Thomas Samuel; Christopher, Solomon; Gravitt, Patti; Abraham, Priya
Abstract : Objective: Human papillomavirus (HPV) contributes to the development of cervical cancer. We hypothesize that HPV DNA and messenger RNA (mRNA) levels may be associated with increasing stages of cervical cancer. Materials and Methods: In this study, we measured DNA and mRNA viral loads of the most common high-risk HPV-16 and HPV-18 in cervical biopsy tissue of women with cervical neoplasia using real-time polymerase chain reaction. Results: Median HPV-16 and HPV-18 DNA viral loads were 58, 342 copies and 71, 367 per 5000 cells, respectively. We found that HPV-16 and HPV-18 DNA levels did not correlate with advancing tumor stage ( P = 0.977 and P = 0.263). Messenger RNA transcripts were detected in 81 (86%) of HPV-16 DNA-positive women and in 16 (84.2%) of HPV-18-positive women. Median HPV-16 and HPV-18 transcript copy numbers were 5964 and 6158, respectively. In women with squamous cell carcinoma, HPV-16 mRNA loads showed an increasing but not statistically significant trend with advancing disease stage ( ρ = 0.231, P = 0.058). Conclusions: We conclude that HPV mRNA levels and not DNA levels may be associated with advancing stages of cervical cancer.